2019
DOI: 10.3390/ijerph16060941
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Biological Components of Urban Aerosols in Africa: Current Status and Knowledge Gaps

Abstract: Aerosolized particulate matter (PM) is a complex mixture that has been recognized as the greatest cause of premature human mortality in low- and middle-income countries. Its toxicity arises largely from its chemical and biological components. These include polycyclic aromatic hydrocarbons (PAHs) and their nitro-derivatives (NPAHs) as well as microorganisms. In Africa, fossil fuel combustion and biomass burning in urban settings are the major sources of human exposure to PM, yet data on the role of aerosols in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 130 publications
0
23
1
1
Order By: Relevance
“…In 2012, the yearly average PM 2.5 levels in South Africa ranged between 4.9 and 43.3 μg m −3 , and for all 21 AAQM stations the annual average was 24.1 μg m −3 (Altieri and Keen 2019). The maximum PM 2.5 level was 39.1 μg m −3 , which is generally lower than those reported in cities from other African countries (deSouza 2020; Kalisa et al 2019;Fayiga et al 2018;Gaita et al 2014;Petkova et al 2013). The mean and maximum PM 2.5 levels were higher than those reported in rural areas of South Africa (Tshehla and Djolov 2018; Novela 2019; Novela et al 2019), but lower than those reported in Pretoria, located about 1600 km north of Cape Town (Morakinyo et al 2019;Adeyemi 2020;Mwase 2020) or the South African towns located in the Vaal Triangle and Highveld air pollution priority areas (Olutola et al 2019).…”
Section: -H Pm 25 Soot and Meteorological Conditionscontrasting
confidence: 57%
See 1 more Smart Citation
“…In 2012, the yearly average PM 2.5 levels in South Africa ranged between 4.9 and 43.3 μg m −3 , and for all 21 AAQM stations the annual average was 24.1 μg m −3 (Altieri and Keen 2019). The maximum PM 2.5 level was 39.1 μg m −3 , which is generally lower than those reported in cities from other African countries (deSouza 2020; Kalisa et al 2019;Fayiga et al 2018;Gaita et al 2014;Petkova et al 2013). The mean and maximum PM 2.5 levels were higher than those reported in rural areas of South Africa (Tshehla and Djolov 2018; Novela 2019; Novela et al 2019), but lower than those reported in Pretoria, located about 1600 km north of Cape Town (Morakinyo et al 2019;Adeyemi 2020;Mwase 2020) or the South African towns located in the Vaal Triangle and Highveld air pollution priority areas (Olutola et al 2019).…”
Section: -H Pm 25 Soot and Meteorological Conditionscontrasting
confidence: 57%
“…Very few studies in Africa reported on PM 2.5 levels (Maenhaut et al 1996 ; Petkova et al 2013 ; Gaita et al 2014 ; Snider et al 2016 ; Fayiga et al 2018 ; Tshehla and Djolov 2018 ; Kalisa et al 2019 ; deSouza 2020 ). No study ever reported on PM 2.5 levels in Cape Town nor investigated its seasonal and weekly variation, chemical composition and possible source region contributions by using backward trajectory cluster analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Viruses may mix with other suspended ultrafine particles, and thus may agglomerate to form particles of various sizes through aggregation condensation of ultrafine particles and nucleation of gaseous precursors [92,93]. It is also well known that particles may serve as vectors for various substances such as pollen and microorganisms, including bacteria, fungi and viruses [94,95]. It has previously been demonstrated that viruses are carried by fine particles.…”
Section: Droplets and Aerosolsmentioning
confidence: 99%
“…exposures. The situation is similar in many other sub-Saharan African countries (Kalisa et al, 2019;Petkova et al, 2013). This lack of monitoring due to resource limitations also hampers scientific understanding of the sources contributing to air pollution in these countries, which is essential to formulating effective environmental management policies.…”
mentioning
confidence: 99%